The Control of Natural Disaster Caused by Slopes Sliding by Means of Stepped Buildings. (2016) - Ilies, Nicoleta-Maria; Farcas, Vasile-Stelian; Cot, Radu-Vasile; Moldovan, Ioana-Madalina
Abstract: The unstable slopes are one of the causes of natural disasters in Romania. A consolidation system, used only for the sliding slope, is, in most of the cases expensive, but as a part of the foundation system for a housing project might bring economic advantages. The analysis started from a practical case of an unstable slope in Cluj-Napoca city. A complex study was performed to establish the mechanical and physical soil properties and a slope stability analysis, with and without the consolidation system. The results obtained were compared in order to check the most valuable solution.